An Unbiased Reexamination of Stock Market Volatility: Discussion - Shiller, Robert (Journal of Finance, 1985)
Robert Shiller, An Unbiased Reexamination of Stock Market Volatility: Discussion, The Journal of Finance, Vol. 40, No. 3, Papers and Proceedings of the Forty-Third Annual Meeting American Finance Association, Dallas, Texas, December 28-30, 1984 (Jul., 1985), pp. 688-689